Uchronia Designing Time - Schmid, Helga (Birkhäuser, 2020)
What time is it? Why should we care? This book critically investigates our contemporary time crisis. The transformation of society from an agrarian to an industrial, and finally an urbanized way of living and working has created a fundamental change in our understanding of time: a 24/7 mentality. The move from natural time to the digital age leads to a fragmentation of time that deeply affects our daily biological and social rhythm. We need a new approach to time to overcome our temporal system of clocks and calendars. This book investigates a new perception of time by exploring the concept of uchronia, a term derived from the Greek u-topos and meaning 'no time' or 'non-time'. Uchronia is a way of questioning, speculating on and designing new kinds of temporal systems that are more about being in tune than on time.